2014
DOI: 10.21512/tw.v15i2.624
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge Management and Entrepreneur’s Knowledge on Innovation and Firm Performance

Abstract: There is lack of evidence from previous studies that examined the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The prior studies show that entrepreneurial performance can lead the firm performance (Chavez et al, 2017;Al-Henzab et al, 2018). Moreover, prior studies argued that entrepreneurial performance is an essential factor for the long term survival and development of the organization (Hartono and Halim, 2014). Al-Dhaafri et al (2016) found that entrepreneurial performance always has a positive influence on organizational performance and can help organizations to achieve competitive advantages.…”
Section: Relationship Between Entrepreneurial and Organizational Perfmentioning
confidence: 99%
See 1 more Smart Citation
“…The prior studies show that entrepreneurial performance can lead the firm performance (Chavez et al, 2017;Al-Henzab et al, 2018). Moreover, prior studies argued that entrepreneurial performance is an essential factor for the long term survival and development of the organization (Hartono and Halim, 2014). Al-Dhaafri et al (2016) found that entrepreneurial performance always has a positive influence on organizational performance and can help organizations to achieve competitive advantages.…”
Section: Relationship Between Entrepreneurial and Organizational Perfmentioning
confidence: 99%
“…Secondly, this study measures the performance of SME entrepreneurs using dynamic capability as a mediator because the significance of the SME sector is increasing gradually. Thirdly, most of the previous studies focused on the other sectors as well as examined the role of knowledge management practices on business performance ( Hung et al, 2010 ; Protogerou et al, 2012 ; Gholami et al, 2013 ) and taken innovation as a mediator variable in the relationship between organizational performance and other factors such as organizational learning, entrepreneurial orientation ( Hartono and Halim, 2014 ; Ferreira et al, 2020a ). Therefore, the relationship between knowledge management practices using dynamic capability as a mediator on entrepreneurial and organizational performance of SMEs is the motivation of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management (KM) terminology has emerged from complexity in the market, competition in technology and changes in customer demands. Knowledge management is the open and planned creation, renewal and implementation of the knowledge assets of the organization considering the people, process and technology elements in order to achieve organizational goals by increasing the knowledge-based efficiency of the organization [3][4][5][6]. Literature on knowledge management shows that successful applications provide benefits such as increased business performance, increased competitive advantage, creation of new business areas and innovation, reduced costs, time savings, and increased decision-making ability to companies.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management puts the best practices through transferring appropriate knowledge as well as aiding the decision makers in many ways in organizations by dealing with different resources (Hartono and Halim, 2014). Darroch (2005) stated that knowledge management has direct influence on innovation and firm performance.…”
Section: Knowledge Management and Informal Entrepreneur Successmentioning
confidence: 99%